2000
DOI: 10.1023/a:1011115809810
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the normal adult brain, glucose provides 90% of the energy requirements as well as substrate for nucleic acid and lipid synthesis. In the present study, effects of ethanol on glucose transporters (GLUT) and glucose utilization were examined in rat brain. Male Sprague-Dawley rats weighing 250-300 gms were given either ethanol 3 gm/kg BW or saline i.p. 4 hrs prior to the animal sacrifice and removal of the cerebral cortical tissue. The cortical plasma membranes analyzed by cytochalasin B binding assay showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition to regulating glucose utilization, insulin stimulates glucose uptake. Glucose uptake is mediated by glucose transporter molecules termed GLUTs (54), and previous studies (55)(56)(57) demonstrated that chronic gestational exposure to ethanol inhibits expression and function of glucose transporter molecules GLUT1 and GLUT3 in the brain. Together, these observations potentially link ethanol-impaired insulin signaling and neuronal loss to deficiencies in uptake and utilization of glucose in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating glucose utilization, insulin stimulates glucose uptake. Glucose uptake is mediated by glucose transporter molecules termed GLUTs (54), and previous studies (55)(56)(57) demonstrated that chronic gestational exposure to ethanol inhibits expression and function of glucose transporter molecules GLUT1 and GLUT3 in the brain. Together, these observations potentially link ethanol-impaired insulin signaling and neuronal loss to deficiencies in uptake and utilization of glucose in the developing brain.…”
Section: Discussionmentioning
confidence: 99%